Dengue Fever with Sever’s Disease: A Case Report - Ahsan, Kamrul; Md Salim; Rahman, Md Habibur; Mandal, Sanchita (Mugda Medical College Journal, 2025)
This report discusses a case of an 11-year-old boy diagnosed with dengue fever and Sever’s disease. The boy reported to the Paediatric Outpatient Department (OPD) of Mugda Medical College Hospital, Dhaka, Bangladesh, with fever, lower limb pain, and abdominal symptoms. He was eventually found to have a positive dengue NS1 antigen and clinical signs consistent with calcaneal apophysitis. Though musculoskeletal symptoms like bodyache, and joint pain are associated with dengue fever, this rare combination was diagnosed incidentally. Atypical manifestations of dengue, termed as ‘expanded dengue syndrome’ which involves isolated organ complications like neurological, hepatic, renal, or cardiovascular issues. They may arise from severe shock, underlying conditions, or co-infections, and can mimic diseases like malaria or enteric fever, making the clinical decision more difficult and mislead the physician’s initial impression1. Severe back pain in dengue fever which is known as break-bone fever is not uncommon. But in this case calcaneal apophysitis or Sever’s disease was observed with heel pain pose a diagnostic dilemma as it persisted after subsidence of dengue symptoms. So far reported Sever’s disease has not been found as association or musculoskeletal complications in dengue related illness in our country ever before. Mugda Med Coll J. 2025; 8(1): 66-68